The Potential Growth of Terrorism in the Age of Artificial Intelligence and The Quranic Response to Counteraction Scenarios - Adi, Habib Maulana Maslahul; Mufidah, Afifah Ikram (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
The sophistication of Artificial Intelligence (AI) has the potential to increase the complexity of terrorism, although AI can also facilitate counter-terrorism efforts. On the other hand, the Quran, as a source of inspiration and guidance for Muslims, encourages Muslim intellectuals to actualize its teachings in response to emerging issues. This article aims to discuss the potential development of terrorism that utilizes AI and to explore the Quranic response to counter-terrorism scenarios in the AI era. The method used is qualitative, categorized as library research based on its data sources. Documentation serves as the main data collection technique. The analysis is conducted inductively, with comparative analysis prior to drawing the conclusion. The findings of this study indicate that the potential development of terrorism through AI includes enhanced cyber-attack capabilities, autonomous weapons, false propaganda dissemination, data exploitation, disruption of vital infrastructure, and recruitment and deepening of radicalization. Furthermore, scenarios for using AI in counter-terrorism and the Quranic response to them include predictive analysis of terrorist activities and identification of radicalization warning signs as preventive measures aligned with the Quranic teaching of sadd aż-żarī’ah, detection of misinformation and disinformation in line with the values in Surah Al-Hujurat [49: 6], moderation and automatic content removal aligned with the values in Surah An-Nisa [4: 148], and counter-narratives to terrorism and extremism aligned with the values in Surah An-Nahl [16: 125]. Therefore, it is also important for Islamic scholars, as successors holding religious authority in Islam, to actively participate in disseminating the values of the Qur’an that reject all forms of terrorism, so they can contribute to combating the growth of terrorism in the AI era.